CAN FINANCIAL LITERACY SAVE US FROM POVERTY? (ResearchJet Journal of Analysis and Inventions, 2021)
The article assesses the current state of financial literacy of the population of the Republic of Uzbekistan. Special attention is paid to the recommendations and suggestions in government and policy documents, including issues of financial literacy of the population. The author's proposals for the introduction of new forms and methods of increasing the financial literacy of the population of Uzbekistan are also presented.